The legacy of Clytemnestra in Homer’s Odyssey - Buttery, Leanne (My University, 2020)
In Homer’s epic, The Odyssey, the author places Clytemnestra in stark opposition to Penelope, the wife of the epic’s hero, Odysseus. Clytemnestra, the wife of King Agamemnon, cheated on her husband and killed him upon his return from the Trojan war; an action that placed her in the category of a ‘bad wife.’ In contrast, Penelope uses her autonomy to stay within the traditional social roles of a good Greek wife. Penelope is compared with Clytemnestra and found equal to her, yet above her in morality – for she never betrays Odysseus. Even though Penelope does not act like Clytemnestra, the consequences of Clytemnestra’s action damage the reputation of not only Penelope but of all women. Despite his trust in Penelope, Odysseus treats her with suspicion until the end of the epic – as if she too may betray him. This paper will explain how the legacy of Clytemnestra’s actions impacted Penelope throughout the rest of the epic. In order to fully contextualize the power of Clytemnestra’s actions, this paper will analyze how the literary representation of women in classical works expressed the belief that women by nature behaved like Clytemnestra. Regardless of the faithfulness of Penelope, she remains under the cloud of a bad wife because all women – even good ones – cannot be trusted.
Presented in absentia on April 27, 2020 at "Student Research Day" at MacEwan University in Edmonton, Alberta. (Conference cancelled)